IMPLEMENTASI ASURANSI USAHA TANI PADI SE-EKS KARESIDENAN PATI DALAM MENGATASI GAGAL PANEN (Studi Kasus : Kabupaten Kudus, Kabupaten Pati dan Kabupaten Rembang) - Gilang Aldila Daniar; Turtiantoro .; Sulistyowati . (Journal of Politic and Government Studies, 2018)
Insurance comes from the word insurance that has the meaning of insurance. Insurance is an agreement between the insured or the customer with the insurer or the insurance company. The insurer is willing to bear the amount of losses that may arise in the future after the insured agreed on the payment of money called the premium. Premium is the money spent by the insured in return for the insurer. Formally, within the law, insurance is defined as an agreement between two or more parties, in which the insurer binds itself to the insured by accepting the insurance premium to provide reimbursement to the insured due to loss, damage or even loss of expected profit.In this research, the Rice Farmers Insurance (AUTP) program, which is a gold program from the central government, is a mainstay for farmers throughout Indonesia. The problems faced by rice farmers are very complex and diverse from the arrival of floods, to pests and plant-eating organisms (OPT) which resulted in farmers experiencing crop failure. Thus thegovernment provides a facility in the form of agricultural insurance in the hope that it can be utilized properly.This research was conducted in 3 regencies of Kudus, Pati and Rembang districts where in each region have different characteristics and various problems. Therefore, the government in cooperation with State Owned Enterprises (SOEs), namely PT.Jasa Indonesia (JASINDO) as the insurance party in charge. In implementing the Rural Farmer Insurance Business program is needed a regular socialization so that farmers in each region can understand and know that this program is very useful for them. Therefore the government is aggressively and actively in disseminating this program with the hope that farmers in the country especially in the 3 districts can contribute in the success of government programs together.Keywords: Insurance, Farming